The effects of neuromuscular training on sand versus hard surfaces on physical fitness on young male tennis players - Fernandez-Fernandez, J.; Nakamura, F. Y.; Boullosa, D.; Santos-Rosa, F. J.; Herrero-Molleda, A.; Granacher, U.; Sanz-Rivas, D. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To examine the effects of a neuromuscular training program combining plyometric exercises with acceleration, deceleration, and change-of-direction drills conducted on sand or hard surfaces on the fitness qualities of young male tennis players.